Submonolayer Quantum Dots for High Speed Surface Emitting Lasers - Ledentsov, NN; Bimberg, D; Hopfer, F; Mutig, A; Shchukin, VA; Savel’ev, AV; Fiol, G; Stock, E; Eisele, H; Dähne, M; Gerthsen, D; Fischer, U; et al. (Nanoscale research letters, 2007)
We report on progress in growth and applications of submonolayer (SML) quantum dots (QDs) in high-speed vertical-cavity surface-emitting lasers (VCSELs). SML deposition enables controlled formation of high density QD arrays with good size and shape uniformity. Further increase in excitonic absorption and gain is possible with vertical stacking of SML QDs using ultrathin spacer layers. Vertically correlated, tilted or anticorrelated arrangements of the SML islands are realized and allow QD strain and wavefunction engineering. Respectively, both TE and TM polarizations of the luminescence can be achieved in the edge-emission using the same constituting materials. SML QDs provide ultrahigh modal gain, reduced temperature depletion and gain saturation effects when used in active media in laser diodes. Temperature robustness up to 100 °C for 0.98 μm range vertical-cavity surface-emitting lasers (VCSELs) is realized in the continuous wave regime. An open eye 20 Gb/s operation with bit error rates better than 10 −12 has been achieved in a temperature range 25–85 °C without current adjustment . Relaxation oscillations up to ∼30 GHz have been realized indicating feasibility of 40 Gb/s signal transmission.